Multi-Effect Desalination Powered by Concentrated Solar Power: A review - Hadi, Ahmed I.; Hammadi, Salman H. (Basrah Journal for Engineering Sciences, 2025)
The desalination market is gradually growing as a result of the significant water scarcity in various regions throughout the world. Concentrated solar power (CSP) can be used to power distillation, which is an effective method for addressing water shortages in areas where there is both a severe lack of water and abundant direct normal irradiation. CSPs are ideal candidates for the advancement of desalination technologies due to their capacity to produce both thermal and electricity energy. This review article offers a comprehensive of the current status of cutting-edge CSP-desalination systems. The paper reviews previously published studies conducted by researchers in the field of multi-effect desalination using concentrated solar collectors, and they are classified into two main types. Exclusively freshwater generation and freshwater / electricity cogeneration. In addition, the paper reviews conventional desalination. This review illustrates that there are numerous prospective methods for integrating desalination systems into CSPs. Potential areas for future investigation in CSP-desalination systems. In particular, the most significant obstacles to be surmounted are lowering the costs and efficiency improvements of solar repayment and desalination equipment. A potential method to expedite the commercialization of these plants is to develop innovative strategies that optimize thermal efficiency and reduce costs. Environmental factors (solar radiation intensity, ambient temperature and wind speed) and design factors (solar field area, number of mirrors, number of stages, steam temperature, steam quantity and pressure) are the main effective parameters that affect the distilled water production process. In general, the CSP desalination systems are environmentally and technically appealing; however, there remains substantial progress to be made in order for these plants to be commercially viable.